Implementation of Musaqah Agreement in Improving the Welfare of Coconut Farmers in Korleko Village, Lombok Timur - Tina Imroatun Azkia; Busaini, Busaini; Unggul Priyadi (Economy and Finance Enthusiastic, 2024)
This study aims to find out how the implementation and contribution of the musaqah contract to improve the welfare of coconut farmers in Korleko Village, Labuhan Haji District, East Lombok Regency. This research uses a qualitative approach and the data collection techniques used are in-depth interview techniques, documentation, and observation. Data collection and determination of research informants using purposive and snowball techniques. The research data source is using primary data. Data checking or validation uses triangulation techniques, namely source triangulation and method triangulation. The results showed that the implementation of the musaqah contract in cooperation in the coconut plantation sector has not fully fulfilled the conditions of the musaqah contract, which is the absence of a time limit for the cooperation agreement. This research also shows that cooperation in the field of coconut farming can make a positive contribution to the welfare of the community.